KELELAHAN DAN KESEHATAN KERJA NELAYAN - Aprilia Yudi Pratiwi; Dedeh Suryani; Sunardji; Andi Hendrawan (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
Republic Indonesia is an archipelago country of 17.000 islands surrounded by the 70% seas. So fair hence if most of coastal area have living as fisherman. The informal sector labor among fisherman not yet obtained optimal health s e ~ c es pecially which deal with his work, such as those which suggested that is obtain get plenary health service (preventive, promote,curative and rehabilifative and also executed comprehensively in health system.This study was a crossectional study locate in Muara dua, penikel village, district of Kampung laul, Cilacap regency, They take a 30 fisherman randomlyThe objective of this study is to describe the occupational fishermen health profile consisted of three components a) work load , b) nutrition status and occupational deseaseThe Result of the study, most of fishermen is over work load , normaly nutrition status and get 1 fisherman occupational desease